Resistance intensity test (RIT): a novel bioassay for quantifying the level of acaricide resistance in Rhipicephalus microplus ticks - Frans Jongejan; Laura Berger; Laura Homminga; Iris Hulsebos; Alita Petersen; Priscila Teixeira Ferreira; José Reck; Guilherme Klafke (Parasites & Vectors)
Abstract Background One bioassay for detecting acaricide resistance in livestock ticks is the adult immersion test (AIT), wherein engorged ticks are briefly immersed into a solution of a particular acaricidal compound and examined for mortality, their egg-laying capacity and offspring hatchability in vitro. Usually, the recommended label dose or an established discriminating dose of an acaricide is used to determine high mortality (≥ 95%) of susceptible tick strains. Such a test intends to detect the presence of resistance in a tick population. However, the adult immersion test does not directly translate the bioassay results to the predicted efficacy in the field. In this paper, we used the AIT as an initial screening bioassay supplemented with the resistance intensity test (RIT), a novel larval-based bioassay, wherein the resistance level can be determined and translated to the expected field efficacy. This was done by adopting World Health Organisation (WHO) guidelines for resistance detection in mosquitoes, which combines a 1 × recommended dose with 5 × and 10 × concentrated doses to reveal low, moderate and high resistance intensity, respectively. Methods Engorged Rhipicephalus microplus ticks were collected from cattle at six different ranches across Rio Grande do Sul, Brazil, as part of the state’s acaricide resistance surveillance program. Groups of adult ticks from each field collection were subjected to the AIT from each field sample. Additionally, engorged female ticks from each ranch were allowed to lay eggs, and their larval progeny aged 14 to 28 days were then used in the RIT. Deltamethrin and a combination of cypermethrin, chlorpyrifos and piperonyl butoxide were used in both tests, and the results were statistically analysed. Results The in vitro efficacy of deltamethrin against adult ticks in the AIT ranged between 8.74% and 25.38%. The corresponding RIT results on their larval progeny indicated a high resistance level. In the immersion test, the in vitro efficacy of the combination of cypermethrin, chlorpyrifos, and piperonyl butoxide against adult ticks ranged between 49.31% and 100%. The corresponding RIT results on their larval progeny indicated a similar response ranging from fully susceptible to low or moderate resistance. The Pearson correlation coefficient (r = 0.883) showed a high correlation between tick mortality at the 1 × recommended concentrations of acaricides in both tests. Conclusions The resistance intensity test is a valuable addition to the range of bioassays currently available for detecting acaricide resistance by determining the level of acaricide resistance. This is relevant to whether or not to continue using a particular acaricidal class for controlling cattle ticks. Graphical Abstract